Structure-Function of the G-protein-Coupled Receptor Superfamily - Katritch, Vsevolod (2012)
During the past few years, crystallography of G protein-coupled receptors (GPCRs) has experienced exponential growth, resulting in structure determination of 14 distinct receptors, 7 of them in 2012 alone. Including closely related subtype homology models, this currently amounts to about 10% coverage of the GPCR superfamily. Agonist-bound active-state structures are now known for the adrenergic, rhodopsin, and adenosine receptor systems, including a structure of the receptor-G-protein complex for the β(2)-adrenergic receptor. Biochemical and biophysical techniques, such as nuclear magnetic resonance (NMR) and hydrogen/deuterium exchange-mass spectrometry (HDX-MS) are providing complementary insights on ligand-dependent dynamic equilibrium between different functional states. High resolution structures such as the 1.8 A adenosine A2a receptor are illistrating the receptor as allosteric machines, controlled not only by ligands, but by sodium, lipids, cholesterol, and water. This wealth of data is helping to redefine our knowledge of how GPCRs recognize such a diverse array of ligands and transmit signals 30 angstroms across the cell membrane, also shedding light on a structural basis of GPCR allosteric modulation and biased signaling.